Assessment of Biochemical Variables of Medical Importance in Patients of Oral Sq. Cell Carcinoma (OSCC) Using Betel Nuts - Ali, Hania; Tahir, Farah Naz; Tariq, Iqra; Ahmed, Atiq; Iqbal, Waseem; Iqbal, Javeid; Asim Rana, Muhammad; Hafeez, Mansoor (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Betel nut is considered one of the leading causes of oral cell carcinoma. After caffeine, alcohol and tobacco, the betel nut mastication is the fourth most used drug in the world. Aim: To evaluate the fluctuating levels of oxidative stress markers in patients of oral squamous cell carcinoma (SCC) using betel nuts. Study design: Case control study Place and duration of study: University of Lahore Teaching Hospital, Lahore from 21st January 2021 to 10th July 2021. Methodology: One hundred participants recruited and divide into two groups. First group consisted of confirmed cases of oral SCC on histopathological evidence and fifty age and sex matched normal healthy subjects were taken as a control in group B. Oxidative stress markers malondialdehyde (MDA), Isoprostanes, 8- hydroxy deoxyguanosine (8-OHdG), and 4-hydroxynonenal (4-HNE) were measured in both groups by using ELISA and TBRAS methods. Results: Significant difference in oxidative stress markers in oral cell carcinoma patients and control group. The p value differed significantly for MDA, Isoprostanes, 8-OHdG and 4-HNE in serum (p= 0.021, 0.033, 0.001, and 0.000 respectively) as well as in saliva samples (p= 0.011, 0.021, 0.011 and 0.001 respectively). Conclusion: The oxidative stress markers like MDA, Isoprostanes, 8-OHdG and 4- HNE are significantly elevated in patients of oral squamous cell carcinoma as compared to the normal healthy individuals.